Advanced feedback methods in information retrieval - Salton, Gerard 1927-1995; Fox, Edward Alan 1950-; Voorhees, Ellen (1983)
Automatic feedback methods may be used in on-line information retrieval to generate improved query statements based on information contained in previously retrieved documents. In this study automatic relevance feedback techniques are applied to Boolean query statements. The feedback operations are carried out using both the conventional Boolean logic, as well as an extended logic producing improved retrieval effectiveness. Experimental output is included to evaluate the automatic feedback operations.